Consideraciones Éticas en la Gestión de Proyectos. Análisis de Contexto. - Castro Silva, Hugo Fernando (Revista Daena: International Journal of Good Conscience, 2026)
Project management is one of the disciplines with more evolution in recent years with regard to education, best practices standards and certifications (Helgadóttir, 2008). However, as an emerging profession but with some degree of maturity, must face several challenges such as consolidating an ethical framework for action for its practitioners. This work focuses on the analysis of ethical considerations in context of project management. The analysis can contribute to the understanding, by governments, professional organizations, educational institutions, researchers and project managers about the ethical requirements of the profession of project management, considering the project manager as a change agent with soft skills related to leadership and development of a team of collaborators and negotiation processes with different stakeholder groups, which generate conflicting ethical issues throughout the project life cycle. Likewise, discussion and analysis allow recommending to institutions, researchers and professionals in project management, ethics aimed at positioning the body of knowledge of the discipline.